Rock glaciers in crystalline catchments: Hidden permafrost‐related threats to alpine headwater lakes. (4th December 2017) - Ilyashuk, Boris P.; Ilyashuk, Elena A.; Psenner, Roland; Tessadri, Richard; Koinig, Karin A.
Abstract: A global warming‐induced transition from glacial to periglacial processes has been identified in mountainous regions around the world. Degrading permafrost in pristine periglacial environments can produce acid rock drainage (ARD) and cause severe ecological damage in areas underlain by sulfide‐bearing bedrock. Limnological and paleolimnological approaches were used to assess and compare ARDs generated by rock glaciers, a typical landform of the mountain permafrost domain, and their effects on alpine headwater lakes with similar morphometric features and underlying bedrock geology, but characterized by different intensities of frost action in their catchments during the year. We argue that ARD and its effects on lakes are more severe in the alpine periglacial belt with mean annual air temperatures (MAAT) between −2°C and +3°C, where groundwater persists in the liquid phase for most of the year, in contrast to ARD in the periglacial belt where frost action dominates (MAAT < −2°C). The findings clearly suggest that the ambient air temperature is an important factor affecting the ARD production in alpine periglacial environments. Applying the paleoecological analysis of morphological abnormalities in chironomids through the past millennium, we tested and rejected the hypothesis that unfavorable conditions for aquatic life in the ARD‐stressed lakes are largely related to the temperature increase over recent decades, responsible for the enhanced release of ARD contaminants. Our results indicate that the ARDs generated in the catchments are of a long‐lasting nature and the frequency of chironomid morphological deformities was significantly higher during the Little Ice Age (LIA) than during pre‐ or post‐LIA periods, suggesting that lower water temperatures may increase the adverse impacts of ARD on aquatic invertebrates. This highlights that temperature‐mediated modulations of the metabolism and life cycle of aquatic organisms should be considered when reconstructing long‐term trends in the ecotoxicological state of lakes. Abstract : Degrading permafrost can produce acid rock drainage (ARD) in areas underlain by sulfide‐bearing bedrock. Limnological and paleolimnological approaches were used to assess and compare ARDs generated by rock glaciers and their effects on alpine lakes. We argue that ARDs are more severe in the alpine periglacial belt where groundwater persists in the liquid phase for most of the year in contrast to ones where frost action dominates. The frequency of chironomid morphological deformities was significantly higher during the Little Ice Age than during pre‐ or post‐LIA periods, suggesting that lower temperatures may increase the adverse impacts of ARD on invertebrates.